Changing Faculty Employment at Four-Year Colleges and Universities in the United States - Liang Zhang; Ronald G. Ehrenberg; Xiangmin Liu (Institute for the Study of Labor (IZA), 2015)
We use panel data models to examine variations and changes in faculty employment at four-year colleges and universities in the United States. The share of part-time faculty among total faculty has continued to grow during the last two decades, while the share of full-time lecturers and instructors has been relatively stable. Meanwhile, the share of non-tenure track faculty among full-time faculty has been growing, especially among the professorial ranks. Dynamic panel data models suggest that employment levels of different types of faculty respond to a variety of economic and institutional factors. Colleges and universities have increasingly employed faculty whose salaries and benefits are relatively inexpensive; the slowly deteriorating financial situations at most colleges and universities have led to an increasing reliance on a contingent academic workforce. A cross-sectional comparison of the share of full-time non-tenure track faculty also reveals significant variations across institutions.
Keywords: I23; J23; 330; faculty employment; non tenure-track faculty